2018
DOI: 10.1093/ee/nvy140
|View full text |Cite
|
Sign up to set email alerts
|

Foraging Phenology of the Fungus-Growing Termite Odontotermes formosanus (Blattodea: Termitidae)

Abstract: Fungus-growing termites are major contributors to litter decomposition and an agriculture pest in tropical and subtropical Africa and Asia. The foraging behavior of fungus-growing termites was hypothesized to be seasonal and may associate with climatic factors and the occurrence of natural enemies. In this study, we tested the effects of climatic factors and the presence of ants on the foraging activity of the fungus-growing termite Odontotermes formosanus (Shiraki) (Blattodea: Termitidae). Termite-foraging ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…Forage substrate use by fungus-growing termites found in the literature (for a full list of all references and their reported findings, see Table S1 [5,74,75,77,78,79,80,81,82,83,84,85,88,89,90,91,92,93,94,95,96,97,98,99,100,101,102,103,104,105,106,107,108,109,110,111,112,113,114,115,116,117,118,119,120,121,122,123,124,125]) mapped on a schematic phylogeny of the subfamily [35]. Species given the same species name or labelled sp.…”
Section: Figurementioning
confidence: 99%
“…Forage substrate use by fungus-growing termites found in the literature (for a full list of all references and their reported findings, see Table S1 [5,74,75,77,78,79,80,81,82,83,84,85,88,89,90,91,92,93,94,95,96,97,98,99,100,101,102,103,104,105,106,107,108,109,110,111,112,113,114,115,116,117,118,119,120,121,122,123,124,125]) mapped on a schematic phylogeny of the subfamily [35]. Species given the same species name or labelled sp.…”
Section: Figurementioning
confidence: 99%
“…In addition, we found that the number of samples with termites was positively correlated with mean annual temperature (Table S8). Since termites are ectotherms and foraging activity generally scales with temperature (Chiu et al, 2018;Fei & Henderson, 2002), the negative effects of increasing minimum temperature on termite foraging intensity could also be mediated by lower mean annual temperature, as we found a negative relationship between minimum temperature and mean annual temperature ( Figure S6).…”
Section: Consistent Effects Of Temperature and Inconsistent Effectsmentioning
confidence: 64%
“…Specifically, Odontotermes termites often build their foraging galleries in dead branches, twigs and other plant debris lying on the ground, and are rarely active on the surface during the day. Thus, they remain protected against epigeic predators (Uys, 2002; Chiu et al ., 2018; Da Costa et al ., 2019). It is difficult for a small arthropod predator to penetrate the wall of these termite galleries, but if a gallery is damaged by other animals (e.g., foraging antelope) or due to heavy rainfall, an access point to foraging termites is made available.…”
Section: Discussionmentioning
confidence: 99%